UTILIZATION OF TOK TIK AS MEDIA CAMPAIGN MOVEMENT OF WASHES IN INDONESIA FOR PREVENTION OF SPREAD OF VIRUS COVID-19 - Togi Prima Hasiholan; Rezki Pratami; Umaimah Wahid (Metakom, 2020)
Indonesia, which is 64.8% of the population, has used the Internet and 160 million people are social media users, making Indonesia a promising market by social media industry players, such as the Tik Tok application. In 2020 the Tik Tok application became a popular culture in Indonesia, because the Indonesian people would know this application and become its user. The popularity of Tik Tok in Indonesia became an ideal medium by the World Health Organization (WHO) which campaigns for the correct hand washing movement to break the transmission of the COVID Virus -19 or known by the name of corona by producing videos and hashtags #safehands challenge in the Tik Tok application, then the creators produce their own version of video content and add hashtags #safehands challenge to follow this challenge. This type of research used in this study is a qualitative method with a descriptive approach. Tik Tok as a popular media becomes an ideal media in conducting handwashing campaigns which are used by WHO through the hashtag #safehands challenge, but users prefer videos with professional themes in their fields (such as doctors in this case) but light and not patronizing.